2018
DOI: 10.1080/00103624.2018.1495726
|View full text |Cite
|
Sign up to set email alerts
|

A rapid-test for screening biochar effects on seed germination

Abstract: We developed a rapid-test to screen for effects of biochar on seed germination and soils. Crop seeds were placed in containers and covered with 15 g of soil with 1% biochar by weight. Two agricultural soils from South Carolina USA were used. Eighteen biochars were produced from six primary feedstocks [pine chips (PC), poultry litter (PL), swine solids (SS), switchgrass (SG); and two blends of PC and PL, 50% PC/50% PL (55), and 80% PC/20% PL (82)]. Each feedstock was pyrolyzed at 350, 500 and 700°C. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…This suggests that an increase in pH with addition of biochar can be related to reduced plant Zn concentration. As indicated earlier, in a seed germination study we found a general increased soil pH with the same biochars, biochar level, and soils as in this study, with the greatest increase with PL pyrolyzed at 700°C (Olszyk et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This suggests that an increase in pH with addition of biochar can be related to reduced plant Zn concentration. As indicated earlier, in a seed germination study we found a general increased soil pH with the same biochars, biochar level, and soils as in this study, with the greatest increase with PL pyrolyzed at 700°C (Olszyk et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Biochar nutrients. The manure-based biochars (PL and SS) generally had higher nutrient concentrations (Olszyk et al, 2018, Table 3). The SS biochars had the highest Cu, Fe, Mg, Mn, P, and Zn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the DM content of shoot biomass increased in biochar treatments compared to the CON. A positive effect of biochar on shoot dry weight was also reported in a previous study [66]. This can be explained by the addition of mineral nutrients from biochar ash [67].…”
Section: Effects Of Corncob Biochar On Dry Matter Content Of the Shoosupporting
confidence: 85%
“…The uppermost horizon (∼0-23 cm) of both soil profiles was use in this study. Site cultivation history, crop management, and additional characteristics of the soils are described elsewhere (Novak et al, 2014;Olszyk, Shiroyama, Novak, & Johnson, 2018;Olszyk et al, 2020;Sigua et al, 2014) and are summarized in Table 1. After collection, both soils were air-dried and sieved.…”
Section: Core Ideasmentioning
confidence: 99%